2015
DOI: 10.1002/smll.201501413
|View full text |Cite
|
Sign up to set email alerts
|

A S‐Layer Protein of Bacillus anthracis as a Building Block for Functional Protein Arrays by In Vitro Self‐Assembly

Abstract: S‐layer proteins create a cell‐surface layer architecture in both bacteria and archaea. Because S‐layer proteins self‐assemble into a native‐like S‐layer crystalline structure in vitro, they are attractive building blocks in nanotechnology. Here, the potential use of the S‐layer protein EA1 from Bacillus anthracis in constructing a functional nanostructure is investigated, and apply this nanostructure in a proof‐of‐principle study for serological diagnosis of anthrax. EA1 is genetically fused with methyl parat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…39 In an extended study, we developed an S-layer-based 2D nanoenzyme array for the highly sensitive detection of anthrax antibodies by the self-assembly of EA1 in vitro. 40 We also found that EA1 existed on the surface of B. anthracis spores and vegetative cells, and our mAbs could be used for the species-specific and direct detection of both B. anthracis spores and vegetative cells. These mAbs's laid the foundation for the development of several biosensor platforms for the direct detection of B. anthracis spores.…”
Section: Anthracismentioning
confidence: 52%
See 1 more Smart Citation
“…39 In an extended study, we developed an S-layer-based 2D nanoenzyme array for the highly sensitive detection of anthrax antibodies by the self-assembly of EA1 in vitro. 40 We also found that EA1 existed on the surface of B. anthracis spores and vegetative cells, and our mAbs could be used for the species-specific and direct detection of both B. anthracis spores and vegetative cells. These mAbs's laid the foundation for the development of several biosensor platforms for the direct detection of B. anthracis spores.…”
Section: Anthracismentioning
confidence: 52%
“…After several rounds of panning with B. anthracis spores (positive) and B. cereus spores (negative), several mAbs’s with high selectivity and sensitivity were obtained, and the S-layer protein, EA1, was identified as the target antigen . In an extended study, we developed an S-layer-based 2D nanoenzyme array for the highly sensitive detection of anthrax antibodies by the self-assembly of EA1 in vitro . We also found that EA1 existed on the surface of B. anthracis spores and vegetative cells, and our mAbs could be used for the species-specific and direct detection of both B. anthracis spores and vegetative cells.…”
Section: Biosensors For B Anthracis Sporesmentioning
confidence: 83%
“…The unit cell parameters derived from the projection maps were a = 69 Å, b = 83 Å, and γ = 106 • for EA1 and a = 184 Å, b = 81 Å, and γ = 84 • for the Sap array. More recently, in vitro re-crystallized S-layer projection maps were calculated for EA1 [104] and Sap [19]. While the resolution and unit cell parameters were comparable for EA1, the new Sap diffraction map showed a slightly larger unit cell of a = 211.4 ± 1.9 Å, b = 89.1 ± 0.7 Å, and γ = 84.0 ± 1.0 • , an about 10% size discrepancy possibly due to the different behavior of the S-layers in negative stain and electron cryo-microscopy.…”
Section: The Proteinaceous Armor: the S-layermentioning
confidence: 99%
“…S-Layer protein (SLP) is a biologically active protein with an architecture that consists of regular two-dimensional crystalline arrays and exists in Gram-positive and Gram-negative bacterial cell walls. , SLP has many physiological functions such as immune regulation, maintenance of bacterial morphology, cell adhesion, and receptor recognition. , Previous studies have shown that SLP can self-assemble into a native-like S-layer crystalline structure on solid surfaces and interfaces . This self-assembling property of SLP can make it applicable in synthetic biology, biomimetics, and nanotechnology. , In fact, Sleytr et al had proposed that SLP-coated liposomes could be potential vaccine carriers. However, most reports on SLP-coated liposomes were bacillus protein. As food-grade and potentially probiotic organisms, lactobacilli are excellent candidates for health-related applications for their ability to survive in the gastrointestinal tract .…”
Section: Introductionmentioning
confidence: 99%